Verifiable outsourcing private key generation algorithm in an identity-based encryption scheme - Ren, Yan-Li; Cai, Jian-Xing; Huang, Chun-Shui; Gu, Da-Wu (Tongxin Xuebao, 2015)
An identity-based encryption scheme with verifiable outsourcing private key generation algorithm was proposed where the PKG outsourcers the task of private key generation to the server, and could verify the correctness of the outsourcing result effectively. The distinguish ability of the cipher text and verifiability of the outsourcing result was proved without random oracles, and the proposed scheme was realized in a simulation environment. The experiment shows that the cost of the PKG is smaller than that of the servers, and it is much smaller than that of computing the private keys of all users directly.